A STUDY TO ASSESS THE PRACTICE LEVEL REGARDING NEEDLE STICK INJURY AMONG NURSING STUDENTS IN CHERRAAN’S COLLEGE OF NURSING AT COIMBATORE - Mr.K.Jayaprakash M.Sc(N); Mr.Mohanraj.S , Mr.Ramesh.P ,Mr.Rameshraj.S ,Mr.Vishwa.M , Ms.Premalatha.G , Ms.Pushpalatha.S , Ms.Sneha.M , Ms.Sowmiya.A ,Ms.Vishalini.M (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Statement of the problem A study to assess the practice level regarding needle stick injury among nursing students in cherraan’s college of nursing at Coimbatore was undertaken by a group of students in partial fulfillment of the requirement for the degree of Bachelor of Nursing during the year 2022. Objectives of the study To assess the practice level to prevent needle stick injury among nursing students. To identify the association between selected variables such as age, sex, educational qualification, surgical details and knowledge and practice level among nursing students. Research design and method The research approach adopted for the study was qualitative . The conceptual framework adopted for the present study was based on general adoption system . The data was collected from 2nd year B.Sc Nursing students selected by non probability convenience sampling technique to assess the practice level regarding needle stick injury among nursing students. Result Descriptive statistical methods like mean, percentage, standard deviation and inferential statistics liked ‘ t ‘ test and chi-square was used to analyze the collected data. The percentage distribution of students according to demographic variables, majority of them 25 (83.33%) were in the age of 19-20 years, 16 (53.33%) were in the gender of female, 11 (36.66%) were in the monthly income of >10k, 23 (76.66%) were in family type of nuclear family, 22 (73.33%) were in area of rural, 17 (56.66%) were in father occupational status of self employee, 13 (43.33%) were in mother occupational status of un employee, 22 (73.33%) were in father educational status of 1o&2o Education, 17 (56.66%) were in mother educational status of 1o&2o Education, 20 (66.66%) were in know about needle stick injury of yes, 27 (90%) were in previous needle stick injury of no. The pre-test mean level of knowledge score was 13.63 with SD of 2.08. After the intervention, the post-test mean level of knowledge score was 13.33 with SD of 2.58. The mean difference between the pre-test and post-test was 0.30. Paired t test was employed and the calculated t value was 1.08 which indicates the significant difference between pre-test and post-test level of knowledge score at 0.05 level. Hence, this finding shows that the practice has a significance effect in increasing the level of practice among practice level regarding Needle stick injury. Conclusion It was found that the main conclusion of the presents study status that in the pre-test, most of the students had adequate knowledge on needle stick injury. Effectiveness to improving in their knowledge. The study results show that there is significant association between the level of practice with their selected demographic variables. These the variables calculated by chi square test at p<0.05, therefore the investigator was proved the hypothesis is accepted for this study.